A STUDY ON INSTITUTIONAL ENVIROMENT OF THE MODEL SCHOOLS OF TEA GARDEN AREAS OF LAKHIMPUR DISTRICT, ASSAM - Ekka, Jeni; Chaliha, Asomi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The National Policy on Education 2020 aims to transform the Indian education system by making it more inclusive, holistic and flexible. In continuations the Government of Assam launched a significant initiative in October 2020 to establish 119 Model Schools across major tea growing districts through Public-Private- Partnership (PPP). By May 2022, 97 of these schools were inaugurated marking a pivotal step towards providing quality education within tea garden community. The present study, through qualitative research methods , examined the institutional environment in enhancing Enrolment, Attendance and Community participation in the Model Schools in the Tea Garden areas of Lakhimpur district, Assam.